Development of the porcelain tiles by the partial substitution of feldspar with fly ash - Alwi Kutty, Nur Azureen (2020)
Fly ash properties are unusual among engineering materials. Typically used for embankment construction, fly ash is well known in the production of cement, concrete and brick. Fly ash is one of the palm oil waste products from the combustion of palm fiber and shells in the boiler which are collected at the multi-cyclone collectors. In this research, feldspar is gradually replaced by fly ash compositions of 0 – 25 wt. %. The samples were mixed for 12 hours, pressed with a load of 3 tonnes and isostatically pressed by using CIP with a pressure of 100 MPa. The samples were sintered at the temperature range of 1100 – 1300 °C. An investigation on the physical and mechanical properties as well as the crystalline phase and microstructure of porcelain were evaluated in this study. Through XRF analysis, the presence of fluxing component in fly ash significantly proved its potential as fluxing agent in porcelain. The highest strength of the porcelain obtained at the replacement of 5 wt. % of fly ash sintered at 1250 °C concurrently shows it as the best composition of fly ash and the best sintering temperature. Maximum compressive strength of 105.40 MPa and higher Vickers microhardness value obtained through this composition. In fact, the percentage of the total mass loss was increased up to 9.30 %. The bulk density value of the porcelain is reduced to 2.34 g/cm3, which almost 2.5 % loss of density. Lower apparent porosity achieved at this compositions with 0.22 %, indicating almost complete densifications takes place. The percentage of mullite content was found to be increased with existence of fly ash in porcelain compositions. SEM studied revealed that intense interlocking and uniform distribution between the primary and secondary mullite in glassy matrix are contributed in achieving higher densification of porcelain. It is concluded that the utilization of fly ash as fluxing component is highly suitable in porcelain and the replacement of 5 wt. % of fly ash successfully improvised the properties and the microstructure of the porcelain with attaining higher mechanical strength.